Eleição de diretores escolares no município de São Carlos: propostas e polêmicas. - Souza, Dalgisa dos Santos Brito de (2005)
This work approaches the theme of Democratic Management focusing on the question of a School Director election. We questioned about which were the implications involved in the process of electing directors and whether this process contributed to the democratisation of school management. Our aim was to analyse and discuss the open election process for school principals that took place in municipal institutions of the São Carlos municipal teaching network, which it was the first attempt of filling these positions in São Carlos. In order to carry out this research, we started analysing documents such as: the guidelines for the election, which were published as a degree, the final report on the election process, and the data was also collected using semi-scripted interviews, carried out in two stage. At first stage, the researcher analised data regarding the work done by group of Public Policies and Education Management group at UFSCar (Federal University of São Carlos) in cooperation with the General Office Municipal of Education. This data is about the studentes parents , teachers , principals and workers insight, as to the election. In the second stage of collecting data, we interviewed again the same principals, although some of them had already left their jobs. In order to better understand this election process, we also obtained data related to the point of view of the council and the Secretary of Education. The results showed us that the case of the principals was not renewed; the period in which the process was carried out was very short; the participation in debates throughout the presentation of proposals was low. Thus the election process favoured the participation and the opportunity to choose. To conclude, the open election for school principals in the municipal of Sao Carlos was conflicting representing a contradictory case as the data collected showed progress and failures related to the experience of the process and also to the fact that there was not another election process and it still went back to what it was before an indication as a way of choosing the school principal.